IMPLEMENTASI TEKNIK WDEP DALAM PENDEKATAN KONSELING INDIVIDU REALITA UNTUK MEREDUKSI NOMOPHOBIA PADA SISWA KELAS XI SMA 1 KRISTEN SURAKARTA TAHUN AJARAN 2025/2026 - Boas, Georgia; Sri Suryanti, Hera; Adi Putro, Eko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of individual counseling services using the WDEP technique within the reality counseling approach in reducing nomophobia among students of class XI SMA Kristen Surakarta in the 2025/2026 academic year. Nomophobia is a condition of excessive anxiety experienced when individuals are unable to access their mobile devices, which negatively affects learning concentration, time management, and social interaction. This research employed the Guidance and Counseling Action Research (PTBK) method conducted in three cycles, with each cycle consisting of planning, action implementation, observation, and reflection stages. The WDEP technique was applied to help students understand their desires, evaluate their mobile phone usage behavior, and develop more adaptive action plans. The results of the study indicate a gradual and significant decrease in students' nomophobia levels. In the pre-cycle stage, the percentage of nomophobia was 83.33%, which then decreased to 65.73% in Cycle 1, 45.37% in Cycle II, and reached 28.69% in Cycle III. The reduction to below 30% indicates that the research success indicators were achieved. Therefore, it can be concluded that individual counseling using the WDEP technique is effective in helping students reduce nomophobic behavior and improve self-regulation in healthier and more responsible mobile phone use.